Genetic algorithm-based optimization in 4th order Sallen Key high pass filter - Cheng, Khye Lun; Neoh, Siew Chin, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org